2022
DOI: 10.1002/hsr2.516
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Impact of COVID‐19 pandemic on routine vaccination coverage of children and adolescents: A systematic review

Abstract: Background and Aims Scientists and healthcare workers have expressed their concerns on the impacts of the COVID‐19 pandemic on vaccination coverage in children and adolescents. Therefore, we aimed to systematically review the studies addressing this issue worldwide. Methods We conducted a systematic search of relevant studies using the keywords on databases of PubMed, Web of Science, and Cochrane on May 22, 2021. The identified records were imported into EndNote software and underwent a two‐phase screening pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
2
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(114 citation statements)
references
References 64 publications
4
102
2
6
Order By: Relevance
“…Several observational studies on patients, older populations and healthcare workers associated influenza vaccination with decreased COVID-19 infection rates, hospitalizations, morbidities, and mortalities, suggesting complementary protection by influenza vaccines against COVID-19 ( 6 11 ). A recent systematic review revealed that influenza vaccination increased in demand and acceptability among vulnerable populations during the COVID-19 pandemic ( 12 ). Clinical trials involving concomitant administration of trivalent and quadrivalent (including recombinant) influenza vaccines and COVID-19 mRNA vaccines have also showed no safety concerns or immune interference ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several observational studies on patients, older populations and healthcare workers associated influenza vaccination with decreased COVID-19 infection rates, hospitalizations, morbidities, and mortalities, suggesting complementary protection by influenza vaccines against COVID-19 ( 6 11 ). A recent systematic review revealed that influenza vaccination increased in demand and acceptability among vulnerable populations during the COVID-19 pandemic ( 12 ). Clinical trials involving concomitant administration of trivalent and quadrivalent (including recombinant) influenza vaccines and COVID-19 mRNA vaccines have also showed no safety concerns or immune interference ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Ontime completion of immunization series for pneumococcal vaccine was defined as reception of three doses of pneumococcal vaccine before the child turns 13 months of age 22 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with results from studies emerging on the impact of the COVID-19 pandemic on routine childhood vaccines globally. In North America, studies in the United States of America, and the Dominican Republic have reported a decline of 5-18%, and 10% in vaccination coverage, respectively [20][21][22][23][24] . In South America, studies in Columbia and Brazil have reported a drop in vaccination coverage of 14.4-20% and 10 to 20%, respectively 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the low overall COVID-19 mortality rate in children and adolescents, excess mortality rates were observed mainly but not exclusively in resource-limited critical care settings, and were associated with the presence of ARDS or organ dysfunction at admission, as well as select underlying comorbidities [26,61,62,64,[67][68][69]. In addition to the direct impact of the pandemic on pediatric mortality, the potentially indirect effects of COVID-19 on mortality in this vulnerable age group, stemming from disruptions to health services and preventative measures like routine immunization, should not be neglected [66,[70][71][72].…”
Section: Morbidity and Mortality Of Pediatric Covid-19mentioning
confidence: 99%